Can a carbon permit system reduce Spanish unemployment? - Taran Fæhn; Antonio G. Gómez-Plana; Snorre Kverndokk (Statistics Norway, Research Department, 2005)
This paper addresses the frequently articulated worry for the unemployment impacts of abating CO2 emissions. The Spanish economy is ridden by unemployment rates well above the EU average. At the same time the deviation from EU's intermediate emission goals is more serious than for most other EU countries. We use a CGE model that includes a matching model with two types of labour, and which allows for different pricing rules and returns-to-scale assumptions. Our findings are optimistic. Due to low labour intensity in most of the dirty, Spanish industries, the unemployment rate is hardly affected by introducing an emission permit system. Further, by recycling the sales revenue into reduced labour taxes, unemployment rates fall. Contrary to other studies of Europe, we find that reducing payroll taxes on skilled labour is the most successful in reducing unemployment rates, both through increasing demand and through dampening the supply response to rising wages. All the recycling schemes also generate dividends in terms of welfare, but none offset the abatement costs entirely.
Keywords: D58; J68; Q38; 330; Spanish unemployment; Tax reform; Emission Permit Auctions; Employment dividend; Matching functions; Increasing returns to scale; Computable general equilibrium models.